Development of remarkable fatigue properties of self piercing riveting of HC950/1300HS and AA6082-T6 with conventional rivet - Rui Wang; Peijie Xiao; Hao Li; Hua Song; Houguo Lu; Yu Zhang; Honggui Kan; Jianyu Li; Jie Teng; Shiwei Xu (Journal of Materials Research and Technology)
In this study, microstructural evolution, lap-shear and fatigue strength, and failure mechanism of self-piercing riveting (SPR) joints of HC950/1300HS ultra high strength steel (UHSS) and AA6082-T6 aluminum alloy (Al) sheets were revealed through microhardness tests, metallographic observation, quasi lap shear and fatigue experiments. The results showed that severe work-hardening effect and material flow direction change occurred during SPR forming process. Furthermore, the peak load, energy absorption and fatigue strength limits of the joints were 9.55 kN, 23.12J and 3.41 kN respectively, while the ratio of the fatigue strength limit to the peak static load was 0.357, which indicated the UHSS-Al(SPR) joints with conventional rivets maintain excellent static and fatigue strength.